Singular death-causes contribution to temporal trend-shifts of its major causes in Spain, 1975-2016. (13th November 2019) - Cirera, L; Ballesta, M; Salmerón, D
Abstract: Background: Mortality is the arrow of aggregated individual's life style of living beside the national public health and health care system outcomes. The contribution of specified death-causes to the temporal evolution of its great cause, is targeting the community framework for public health action reduction. Objective: To assess yearly contribution of specified death-causes to temporal trend-shifts of its major death- cause in Spain, 1975 to 2016. Methods: causes of death were selected based on magnitude and relevance in public health. Coding-linkage was established between ICD-9 to 10 revisions. Annual-standardized rates were calculated by the direct method according to the European Standard Population from 1975 to 2016. Linear trend period changes were measured through Joinpoint regression models as annual percentage change (APC) and 95% confidence intervals (CI). Joinpoint v4.0.4 and R v3.2.2 software were used at p < 0.05 for statistically significance level. Results: Neoplasm rates have been going downwards (extreme years came from 162.2/100, 000 inhabitants to 145.5) on ending year-periods of 1995-2008-2016. Lung and colorectal cancers replicated neoplasm shape in lower magnitudes. Cardiovascular displayed two decreasing trajectories in 1975-1993 and 1993-2013, and a last flat stage in 2013-2016, while cardiac ischaemia and ictus crossed their trend periods. Ictus has evolved quite in parallel to cardiovascular disease. Influenza and pneumonia conformed a close profile to respiratory great cause contribution, in different periods: 1975-1988 [-8.03% (-9.08, -6.96%)] and 1988-2016 [-2.38% (-2.85, -1.91%)]. Traffic accidents have been modulating external causes dropping shape with a nonsignificant slope period- trend in the 1994-2001 years. Conclusions: The contribution of any singular causes of death into temporal development of its great causes, is a plausible tool for public health surveillance issues addressed to action. Key messages: The great cause of death in temporal evolution is a moving aggregate result of its singular causes of death components over last time. Inflection-trends years-period of death causes are a plausible tool to public health surveillance.